Fisher effect and real interest rate equalization in selected asian countries - Ling, Tai Hu (2008)
This study investigated the validity of the Fisher effect and real interest rate parity with respect to China in the context of Asian countries (China, Hong Kong, Indonesia, Malaysia, the Philippines, Singapore, South Korea, Thailand, India and Taiwan) by using long-term and short-term interest rates for the period spanning from quarter one of 2001 to quarter three of 2006. Univariate unit root tests and ARDL bounds test for cointegration were used in this study to examine both Fisher effect and real interest rate parity. All in all, this study showed that there was no cointegration relationship between short-term nominal interest rate and expected inflation for the case of Indonesia, Malaysia, the Philippines and China. It is shown that only Hong Kong and China exhibited evidence of cointegration relationship between long-term interest rates and expected inflation rates. In other words, Fisher effect holds for Hong Kong and China. Meanwhile, Indonesia, South Korea, Malaysia, the Philippines, Thailand and Taiwan did not exhibited evidence of cointegration relationship between long-term interest rates and expected inflation rates. This implied that Fisher effect did not hold for these countries. This study showed that there was no long-run relationship between the real interest rates for the case of Indonesia and Malaysia with respect to China real interest rate using short-term interest rates. So, real interest rate parity did not hold. It was shown that more evidence of long-run relationship between the real interest rates of Asian countries with respect to China can be observed for the long-term interest rates. The real interest rates for Indonesia and Taiwan exhibited evidence of long-run relationship with respect to China real interest rate. In other words, real interest rate parity holds for Indonesia and Taiwan. Meanwhile, Hong Kong, Malaysia, the Philippines and Thailand did not exhibited evidence of cointegration relationship. The real interest rate parity did not hold for these countries. Finally, a few policy implications have been highlighted in response to these findings. This information was useful for the central bank to adopt an appropriate monetary policy to control economic behavior. Besides, the banks should set efficient investment strategy in order to prevent unnecessary losses in capital investment. These findings will also benefited to the global investors who intend to do investment in the Asian region.